2011
DOI: 10.1007/s10439-011-0332-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Cardiorespiratory Interactions Based on Joint Symbolic Dynamics

Abstract: Abstract-Cardiac and respiratory rhythms are highly nonlinear and nonstationary. As a result traditional time-domain techniques are often inadequate to characterize their complex dynamics. In this article, we introduce a novel technique to investigate the interactions between R-R intervals and respiratory phases based on their joint symbolic dynamics. To evaluate the technique, electrocardiograms (ECG) and respiratory signals were recorded in 13 healthy subjects in different body postures during spontaneous an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
57
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 50 publications
(47 reference statements)
2
57
0
4
Order By: Relevance
“…'forbidden words') of symbolic patterns complemented information retrieved from spectral analysis in patients threatened by sudden cardiac death [7] and enhanced obstructive apnea screening [8]. This kind of transformation has also been extended to quantify time-delayed couplings between heart rate and blood pressure modulation [9] or to reflect cardiorespiratory interaction [10].…”
Section: Introductionmentioning
confidence: 99%
“…'forbidden words') of symbolic patterns complemented information retrieved from spectral analysis in patients threatened by sudden cardiac death [7] and enhanced obstructive apnea screening [8]. This kind of transformation has also been extended to quantify time-delayed couplings between heart rate and blood pressure modulation [9] or to reflect cardiorespiratory interaction [10].…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, Kabir et al [74] proposed a tertiary symbolization scheme and quantified the relative frequency of word types, capturing RSA patterns and thereby adding physiological a-priori knowledge to the analysis. To address the issue of different frequencies between cardiac and respiratory oscillators, Hilbert transformation was introduced to obtain the instantaneous respiratory phase (RP) sampled at the R peak in ECG, yielding beat-to-beat symbol sequences of changes in RR interval and respiratory phase.…”
Section: Joint Symbolic Dynamics -(Jsd)mentioning
confidence: 99%
“…They are based on the differences between successive R-R intervals (an increase in RR' was represented by "+1", decrease by "−1" and no change by "0") and Rinstant respiratory phases (inspiratory phase was represented by "+1", expiratory phase by "−1" and transition from inspiratory to expiratory phase and vice versa by "0"), as described previously [3].…”
Section: Joint Symbolic Dynamicsmentioning
confidence: 99%
“…Compared to conventional signal-processing approaches which are inadequate for characterizing complex system dynamics, joint symbolic dynamics (JSD) has been shown to be an effective technique to provide enhanced information by employing a coarse-graining procedure to preserve the robust properties of the system's complex dynamics [2,3]. Symbolic dynamics has been widely used to study HRV dynamics and is suggested to provide improved performance for the analysis of respiratory data and cardiorespiratory interaction [3,4].…”
Section: Introductionmentioning
confidence: 99%